2021
DOI: 10.1001/jamaoto.2020.5261
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes of De Novo vs Inverted Papilloma–Associated Sinonasal Squamous Cell Carcinoma

Abstract: IMPORTANCE Overall, the prognosis of sinonasal squamous cell carcinoma (SCC) is poor. This malignancy can arise de novo or from inverted papillomas, but it is unclear whether survival differences between the 2 pathologies exist.OBJECTIVE To assess for survival differences between patients with sinonasal de novo SCC (dnSCC) and those with inverted papilloma-associated SCC (IPSCC).DATA SOURCES A search of Ovid MEDLINE, Embase, Scopus, and the Cochrane Library from inception to January 23, 2020, with cross-refere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 59 publications
3
14
0
Order By: Relevance
“…In many instances, malignant transformation does not occur throughout the entire IP tumor bulk itself, and IP‐SCC may only be discovered during definitive resection, with no reliable way to sample for IP‐SCC ahead of time. The overall 5‐year OS rate calculated from individual survival data extracted from 15 studies was 67%, slightly higher than the 62% aggregate mean 5‐year OS values reported by 17 studies, and similar to the 65% reported by a recent study comparing IP‐SCC and de novo SCC (DN‐SCC) survival 44 . The 5‐year OS of 62% likely reflects a more accurate survival percentage given the higher sample size available for data aggregation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…In many instances, malignant transformation does not occur throughout the entire IP tumor bulk itself, and IP‐SCC may only be discovered during definitive resection, with no reliable way to sample for IP‐SCC ahead of time. The overall 5‐year OS rate calculated from individual survival data extracted from 15 studies was 67%, slightly higher than the 62% aggregate mean 5‐year OS values reported by 17 studies, and similar to the 65% reported by a recent study comparing IP‐SCC and de novo SCC (DN‐SCC) survival 44 . The 5‐year OS of 62% likely reflects a more accurate survival percentage given the higher sample size available for data aggregation.…”
Section: Discussionsupporting
confidence: 57%
“…However, our review suggests IP‐SCC has improved prognosis compared to DN‐SCC. Although reporting on DN‐SCC local and regional recurrence rates are mixed, with some studies finding rates similar to that of IP‐SCC's 23.8% while others finding recurrence rates as high as 56%, primary studies have demonstrated that 5‐year OS for DN‐SCC patients falls between 55.4% and 75% with a recent meta‐analysis placing it at 56%, notably lower than that found of IP‐SCC in the present review 27,29,33,38,44,45 . Whether the contrast in survival and recurrence outcomes can be attributed to differences in tumor biology, tumor stage and grade at presentation, or other factors is yet to be determined.…”
Section: Discussionmentioning
confidence: 50%
“…9,10,59 A recent meta-analysis, for example, reported DN-SCC as a more aggressive tumor portending worse survival outcomes than IP-SCC. 9,60 While this recent meta-analysis, which reported a similar 5-year OS rate (56%) in patients with DN-SCC, focused on survival outcomes between DN-SCC and IP-SCC, it did not assess the impact of treatment and clinical characteristics on survival.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the prognosis for SNSCC is poor, averaging ~40% at 5 years [ 65 ]. Although there is no strong data in the literature, patients with de novo SNSCC have almost a twofold increase in mortality compared with those with ISP-associated SNSCC [ 17 , 66 , 67 ], but this does not translate into any meaningful difference in treatment management.…”
Section: Egfr Ex20ins Targeted Therapiesmentioning
confidence: 99%